Kapitza resistance between superfluid helium and solid: role of the boundary: Сверхтекучий 4He и 3He - Amrit, J.; Ramiere, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Kapitza resistance measurements conducted at T > 1 K on silicon and niobium single crystals in contact with helium demonstrate respectively the importance of atomic scale surface roughness and dislocations due to surface damage at the boundary. Two different experimental configurations were used.